INDEPENDENSI MEDIA TEMPO DAN PENGARUH EKONOMI POLITIK DALAM PRAKTIK STRUKTURASI - Elik Susanto (Jurnal Pustaka Komunikasi, 2021)
This research focused on how Tempo editors apply the principles of independence, maintain credibility, and maintain the integrity of journalists as a media business strategy in the digital age. It is no secret that in the media newsroom there are often conflicts, namely the pull between business interests and editorial attitudes. The opposition heats up as newsroom authorities deal with marketing, advertising sections, business development sections, as well as shareholders in news products. The purpose of this study is to see how the negotiation process and compromise the interests of it. At the end of the day, there are those who win and lose. Research using qualitative method with descriptive approach. In describing the findings, researchers will use inductive theory as a tool of hypothesis, observation, and analysis of Tempo practices applying independence in the influence of political economy structure. The researchers' findings state that in maintaining integrity as an effort to uphold the independence of Tempo is not easy to intervene by anyone when making a report on journalistic products.